Pengembangan E-Modul Berbasis Forward And Backward Chaining untuk Meningkatkan Kemandirian Belajar Siswa - Zul Harfi; Nur Azizah; Annisaul Khairat (Ideas Publishing, 2022)
Only one teaching material is held by the teacher, namely the Al-Qur'an Hadith package book, even though the teacher has a laptop and a school projector as a tool for developing learning media and teaching materials. However, teachers rarely develop the teaching materials they use. This study aims to determine the validity and practicality of e-modules based on Forward and Backward Chaining. The method used is R&D using the ADDIE model. 20 students of class XI IPA are the subject of this research. Questionnaires, practicality sheets, validity sheets, interview guides are the instruments that researchers use in collecting data. E-Modules based on Forward and Backward Chaining that have been developed are then carried out practicality tests and validity tests. Analysis of student needs 90.1% with very high category. The validation result of 89% is categorized as very valid, the practicality result of 88% is stated in the very practical and usable category.